Effect of nano-hydroxyapatite incorporation on the immediate and long-term bond stability of a one-step self-etch adhesive - Bhanu Pratap Valluri; Madhu Varma Kanumuri; Girija Sajjan; Kalyan Satish Rajulapati; Venkata Karteek Varma Penmatsa; Jagapathi Babu Mavidi (Journal of Dental Materials and Techniques, 2025)
Objective: This study evaluated the effect of incorporating nano-hydroxyapatite (nHAp) at various concentrations on the immediate and long-term bond strength of a one-step self-etch adhesive to dentin.Methods: A total of 100 sound maxillary central incisors were collected. The dentin was exposed on the labial surfaces, and the teeth were randomly assigned into two groups (n=50) based on the evaluation time points: 24 hours and 6 months. Each group was further divided into five subgroups (n=10) based on the concentration of nHAp (0, 1, 2, 3, and 4 wt%) incorporated into Adper Single Bond Universal adhesive. Composite resin buildups were formed on dentin using cylindrical molds, and light-cured. Shear bond strength (SBS) was measured by a universal testing machine, and fracture modes were assessed under a stereomicroscope. Statistical analysis was performed using a two-way ANOVA (P<0.05).Results: At 24 hours, the highest bond strength was observed in 2% nHAp (41.68 ± 15.24 MPa), followed by 1% nHAp (36.75 ± 14.24 MPa), both significantly greater than the control group (0% nHAp: 17.03 ± 4.57 MPa; P < 0.05). After 6 months, 2% nHAp again demonstrated the highest bond strength (43.28 ± 6.87 MPa), followed by 1% nHAp (37.00 ± 6.90 MPa), both significantly higher than the control (15.28 ± 4.63) and 4% nHAp groups (14.58 ± 2.33 MPa; P<0.05).Conclusions: The incorporation of nano-hydroxyapatite at concentrations up to 2 wt% into a one-step self-etch adhesive significantly enhanced both immediate and long-term bond strength to dentin.